Improving Knowledge about Drug Use During Fasting through Pharmaceutical Counseling Accompanied by Leaflet - Yuly Peristiowati; Rina Widiyawati (STIKes Patria Husada Blitar, 2025)
Medication use in patients with chronic diseases during Ramadan is a crucial yet often overlooked public health challenge in the primary health care system in Indonesia. Non-compliance with medication regimens and inappropriate dosage adjustments during fasting can lead to serious complications and even medical emergencies, especially in patients with diabetes and hypertension. This community service activity aimed to evaluate the effectiveness of pharmaceutical counseling, accompanied by leaflets, in enhancing patients’ knowledge of medication use during fasting for chronic conditions. This quasi-experimental study was conducted at the Technical Implementing Unit of Kepanjenkidul Health Center, Blitar City, involving 18 patients diagnosed with diabetes and hypertension. The study employed a knowledge questionnaire. The design of this study aims to analyze changes in patient knowledge related to drug use during Ramadan fasting through a structured intervention approach. The results of the activity showed a significant increase in knowledge scores, from an average of 28.33 (pre-test) to 47.11 (post-test), representing a percentage increase of 37.56% (p-value = 0.000, p = < 0.05). In conclusion, pharmaceutical counseling through brochures has shown promise as a strategy for improving patients’ understanding of medication management during Ramadan. It is recommended that health centers develop specific counseling protocols and educational materials tailored to the characteristics of patients, particularly those from low-educated and pre-elderly groups. The implementation of this counseling program needs to be integrated into routine pharmaceutical services, with a focus on preparation several weeks before Ramadan to improve medication safety and therapy fulfillment for patients who choose to fast.